Λογοπαίγνια με κύρια ονόματα στις επιστολογραφικές συλλογές της μεσοβυζαντινής και υστεροβυζαντινής περιόδου (12ος-14ος αι.) - ΓΟΥΣΓΟΥΡΙΩΤΗΣ Γεώργιος (Byzantina Symmeikta, 2023)
This article discusses the puns on proper nouns in ten different letter collections of the middle and late Byzantine period (12th–14th centuries). Specifically, our main aim is not only to showcase the content, the extent and the purpose of these wordplays, but also to offer an insight into their function in the contemporary letter collections and into their own special features